Association between maternal haemoglobin status during pregnancy and children's mental and psychomotor development at 18 months of age: Evidence from rural Bangladesh - Sayedur Rahman; Lina Wallberg; Anisur Rahman; Eva-Charlotte Ekström; Maria Kippler; Jena D Hamadani; Syed Moshfiqur Rahman (Taylor & Francis Group, 2024)
Background Anaemia is commonly caused by iron deficiency and screened by haemoglobin (Hb) concentration in blood. There is a scarcity of longitudinal data on the relationship between maternal Hb levels during pregnancy and neurodevelopment in children. Objective To measure the relationship of maternal Hb concentrations during pregnancy on early child development. Methods This prospective cohort study included 1,720 mother-child dyads in rural Bangladesh. Maternal Hb concentrations were measured at 14 and 30 weeks of gestation. The child's Mental Developmental Index (MDI) and Psychomotor Developmental Index (PDI) at 18 months of age were measured using Bayley Scales of Infant and Toddler Development (BSID-II). Data on socio-demographic characteristics, anthropometrics, mothers' IQ and children's home stimulation were also collected. Bivariate and multivariable-adjusted linear regression analyses were used to explore associations of maternal Hb with child development. Results Mean Hb concentrations at 14 and 30 weeks of gestation were 116.6 g/L (±12.7) and 114.7 g/L (±12.7), respectively. Mean MDI and PDI scores among 18-month-old children were 78.9 (±12.4) and 93.8 (±13.7), respectively. Maternal 14-week Hb concentration was correlated with PDI (r = 0.06; p < 0.05) and 30-week Hb concentrations was correlated with MDI (r = 0.05; p < 0.05). Multivariable adjusted linear regression analysis showed that an increase in 14-week Hb concentrations increased the PDI scores among boys (β = 0.09; 95% CI: 0.02, 0.16). Hb concentrations at 30 weeks of gestation were not associated with MDI or PDI scores. Conclusion Higher maternal Hb concentrations at 14 weeks of gestation were associated with higher PDI among 18-month-old boys in Bangladesh.